Evaluasi Mutu Fisikokimia Beras Hasil Persilangan antara Empat Padi Varietas Unggul dan Padi Liar (Oryza glaberrima dan O. rufipogon) - Siti Yuriyah; Oky Dwi Purwanto; Higa Afza; Ahmad Dadang; Agus Masyuri; Rina Siti Galurina; Dwinita Wikan Utami (Jurnal Ilmu Pertanian Indonesia, 2024)
The physicochemical quality of rice is evaluated to ensure that it is fit for consumption and meets established quality standards. This study aims to analyze the physicochemical properties of rice strains resulting from crosses between four high-yielding varieties of rice and two wild rices so that the appropriate genotype is obtained for the development of quality rice. The research was conducted from November 2019 to March 2020 at the Quality Laboratory, Muara Experimental Garden, Rice Research Center, Bogor. The rice genotypes used were 22 strains resulting from crosses between high-yielding varieties of rice (Ciherang, Inpari 13, Inpari 10, and Situ Bagendit), and wild rice (Oryza glaberrima and O. rufipogon), 4 comparison varieties of crossbred elders, and two comparison varieties of organoleptic tests (Memberamo and IR42). Physical and chemical qualities were observed in terms of grain moisture content, grain density, broken skin rice yield, milled rice yield, head rice yield, rice length, rice shape, and rice liming, amylose content, gelatinization temperature, and organoleptic. The results showed that the strains 44-F-C21, 58-F-C21, and 59-F-C21 provided fairly good rice quality with head rice yields above 80% and higher than their respective elders (Situ Bagendit and Ciherang), and water content below 14%. These strains had characteristic characteristics, namely medium rice form, amylose content of 26.38%, and alkali score of 2-3. Most of these genotypes also exhibited high gelatinization temperatures, medium rice texture, and savory rice flavors. The genotype selected from the results of crosses between high-yielding varieties of rice and wild rice has the potential to be developed because there are genetic improvements from its elders on several physicochemical characteristics of rice. Keywords: amylose content; gelatinization temperature; physicochemical properties; rice lines; wild rice